Development of Hardware and Software for the System of Remote Control of Geometrical Parameters of Railcar Wheelsets - Shapovalov, Ye.V.; Koliada, V.O.; Topchev, D.D.; Lutsenko, N.F.; Mangold, A.M. (Science and Innovation, 2024)
A hardware-software complex for the system of remote control of geometrical parameters of railcar wheelsets has been developed. The system is designed for non-contact scanning of wheel working surface profiles and automatic evaluation of wheelset technical condition during the train movement. The application of results to the railways carriage facilities will significantly improve the qualitative and quantitative control of wear parameters and will raise traffic safety due to timely detection of wheelset dangerous defects.